PENGARUH COVID-19, UKURAN PERUSAHAAN, LEVERAGE, DAN GROWTH TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Natanael, Ryan; Imelda, Elsa (Jurnal Paradigma Akuntansi, 2023)
This research aims to test the effect of COVID-19, firm size, leverage and growth towards firm perfomance of manufacturing companies listed in Indonesia Stock Exchange for the period 2018 to 2020. The sample was chosen using purposive sampling method and the data used are 72 companies and with a total of 216 total data. The data are then processed using multiple linear regression analysis using the software spss (statistical product and service solution) version 26. This research found that firm size and growth both affect firm performance positively and significantly. This research also shows that leverage have a significant but negative effect towards firm performance. Lastly, this research shows that COVID-19 have a negative but insignificant effect towards firm performance.